Cranial and Spinal Subdural Hygroma Following Lumbar Epidural for Labour Analgesia - Elizabeth Thompson; Nicholas Haden; David Hutchins (Research and Practice in Anesthesiology, 2018)
Intracranial hygroma is a rare and probably missed complication of epidural analgesia secondary to accidental dural breech. The patient presented had a presumed spinal cerebrospinal fluid leak with symptoms of intracranial hypotension. Unusually the patient had both an intracranial subdural hygroma and rarely reported extensive spinal intradural (extra-arachnoid) collection following a lumbar epidural, administered in labour. Given the potential for progression to symptomatic neurological deficits, anesthetists should consider subdural hygroma when encountering patients with features of intracranial hypotension, or altered neurology following epidural. Pathophysiology, imaging and management are discussed.